New Coefficients of the Minority Carrier Lifetime and Bandgap Narrowing Models in the Transparent Emitter of Thin Film Silicon Solar Cells - A. Zerga; M. Benosman; F. Dujardin; B. Benyoucef; J-P. Charles (Active and Passive Electronic Components)
In this study we have determined new coefficients for the physical model describing the band-gap narrowing and the minority carriers lifetime. This was accomplished according to the doping level of the thin emitter. This model allows us to take into account both the effects of the heavy doping and the majority carrier degeneration for the very high level of doping. The results we obtain by the corrected model are in good agreement with those reported in the literature and in different experiments. They show us the possibility of accurately evaluating the performances for the n+p silicon solar cell. This model is then used to introduce a new concept for the thin layer emitter, called transparent emitter.